Sustainable Marketing as a Buyer's Motivating Factor in the Retail Business: Example of Georgia - Taktakishvili, Tengiz; Sachaleli, Nino (European Scientific Journal, ESJ, 2024)
In recent years, sustainability has emerged as a significant challenge for the business sector, particularly in the retail industry. Business owners continue to harbor doubts about producing sustainable products, as it requires adjustments to their product segment and marketing strategies. The paper highlights the importance of sustainable marketing in the retail sector and discusses it as a motivating factor from the customersâ€™ perspective. This study focuses on examining the role of sustainable marketing and creating the profile of â€œsustainable buyersâ€ by utilizing a case study of Georgia. In accordance with the quantitative research method, the paper identifies how sustainable marketing influences buyersâ€™ choice and provides evidence for the hypothesis that sustainable marketing serves as a motivational factor in the retail sector, exerting significant influence on the decision-making process.